Social History of Islamic Law from Gender Perspective in Aceh: A Study of Marriage Traditions in South Aceh, Indonesia - Inayatillah, Inayatillah; Mohd Nor, Mohd Roslan; Asy’ari, Asy’ari; Faisal, Muhammad (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2022)
This study aims to examine the social history of Islamic law from a gender perspective in terms of the Samadua marriage traditions in South Aceh. This empirical legal study used a socio-historical approach to Islamic law and gender. The study collected data by means of literature review and in-depth interview. Findings showed that the couples living at the in-law’s house before holding the walīmah al-‘ursy (wedding reception) was a violation of adat (custom) in the Samadua community. The customary sanctions imposed included being completely prohibited to hold walīmah al-’ursy and intat linto/tueng dara baroe (escorting the groom/accepting the bride) procession. From the view of Islamic law, the customary sanctions that apply in the Samadua community are intended to avoid slander and to gain maslāhah (benefit). This is also in line with the principle of sadd al-żarī'ah and does not conflict with the concept of sahih ‘urf. This is because walīmah al-’ursy for women is the time when they are treated with respect and dignity, and this time prayers will also be made for as well as dowry, valuables, and other gifts, making it worth to celebrate. From the perspective of the social history of gender-based Islamic law, the application of this customary sanction also shows that the position of women in Acehnese society is respectable enough that they must be treated with dignity. Because Acehnese women in the past have experienced periods of glory, until now their position and bargaining value are still respectable in customary practices in the Aneuk Jamee community in South Aceh.